Otimização do desempenho dinâmico de robôs paralelos acionados por cabos com redundância cinemática utilizando reposicionamento contínuo - Oliveira, Gabriel Luis (Universidade Federal de São Carlos, 2022)
Parallel robots play a key role in manufacturing processes. Among its classifications, there is a specific type called parallel robot driven by cables (RPAC), which has good inertial properties and relatively low costs. Even so, there may be undesired characteristics, such as the presence of singularities inside the work area, which leads, for example, to loss of rigidity of cables, distribution of forces and vibration. One way to improve the manipulator architecture is through kinematic redundancy, a technique that consists of adding an active joint in one of the kinematic chains of the non-redundant manipulator. Based on that, a numerical model of a cable-driven parallel planar robot was implemented in MATLAB software and the impact of kinematic redundancy was defined through a continuous repositioning of the redundant joints. It was possible to compare different redundancy resolution strategies through an optimization algorithm, in order to minimize the forces acting on the cables during the execution of the trajectory, as well as to understand the influence of the rotation of the end-effector on these values. The results showed an improvement in the dynamic performance of the redundant manipulators compared to the non-redundant model, in addition to comparing between the redundant models which strategy was more assertive.
Dynamic performance optimization of cable-driven parallel robots with kinematic redundancy using ongoing repositioning
Keywords: Redundância cinemática; Robôs paralelos acionados por cabos; Otimização; OUTROS::ENGENHARIA MECATRONICA